GH Responsiveness Is not Correlated to IGF1 P2 Promoter Methylation in Children With Turner Syndrome, GHD and SGA Short Stature - Apel, Anja; Iliev, Daniel I.; Urban, Christina; Weber, Karin; Schweizer, Roland; Blumenstock, Gunnar; Pasche, Sarah; Nieratschker, Vanessa; Binder, Gerhard (Frontiers in Endocrinology, 2022)
Background The methylation of IGF1 promoter P2 was reported to negatively correlate with serum IGF-1 concentration and rhGH treatment response in children with idiopathic short stature. These findings have not yet been confirmed. Objective This study aimed to determine IGF1 promoter P2 methylation in short children treated with rhGH and correlate clinical parameters with the methylation status. In addition, long-term stability of methylation during rhGH treatment was studied. Design This was a single tertiary center study analyzing clinical GH response and IGF-1 serum concentration changes in patients with GHD (n=40), SGA short stature (n=36), and Turner syndrome (n=16) treated with rhGH. Data were correlated to the methylation of two cytosine residues (-137, +97) of the P2 promoter of IGF1 in blood cells measured by pyrosequencing in 443 patient samples. Results Basal and stimulated IGF-1 concentrations, first year increment in height velocity and studentized residuals of a prediction model did not correlate to the methylation of -137 und +97 in IGF1 P2 promoter. The methylation of these two sites was relatively stable during treatment. Conclusions This study did not confirm IGF1 P2 promotor being a major epigenetic locus for GH responsiveness in patients treated with a normal dose of rhGH. Additional studies are warranted.